SLOW DEEP BRETHING TECHNIQUE ON NY.Y TO REDUCE ANXIETY IN PROSPECTIVE IUD ACCEPTORS AT RS. HJ BUNDA HALIMAH - Karlina Karlina (MEDIS: Jurnal Riset Ilmu Kesehatan, 2024)
The intrauterine device resembles the letter T. This birth control is installed in the uterus as a barrier to sperm when going through the process of fertilization. Generally, there are two forms of the IUD. Namely, there is an IUD with copper material; for example, this type of ParaGard type has durability with a period of 21 years, and an IUD that has hormones in its content, such as Mirena and on this IUD must be replaced with a better one at the time of five years of use. However, it has various advantages, but the coverage that uses the IUD still needs to be improved. The reason is that women of childbearing age do not want to use this birth control method because the use of the IUD makes the patient anxious to increase. Treating slow deep breathing techniques carried out in a way that is in the position of the IUD KB acceptor sitting or lying down will cause sympathetic nerve activity to decrease, parasympathetic nerves to increase, and body relaxation to increase until anxiety in KB acceptors to be reduced. The purpose of the slow breathing action is to analyze whether the slow deep breathing technique affects anxiety to decrease and not be anxious, which is carried out on prospective IUD acceptors at Hj. Bunda Halimah Hospital. Data collection was carried out before and after being given an intervention to overcome anxiety problems on 21 February 2024 at 13.50 WIB, namely with acceptors trained to hold their breath for three seconds, pursing their lips, and exhaling through their mouth slowly for 6 seconds. Feel the stomach move down. Encourage acceptors to repeat these steps 5-7 times for 15 minutes. The measuring tool for anxiety levels in acceptors in this study is the Hamilton Anxiety Rating Scale questionnaire ab, abbreviated as HARS, measuring instruments used before and after slow breathing action. This study concludes that the technique used in giving slow, deep Breathing to Mrs. Y is an effort to reduce anxiety in prospective IUD acceptors at Hj Bunda Halimah Hospital.